Release film, resin composition, and method for producing resin composition
By adding trace silicone resin to the polyolefin resin, the problems of deformation and thermal deterioration during the heating and stretching process are solved, and the advantages of lightweight, film-forming properties and whiteness are achieved, and the recycling properties of the material are improved.
Patent Information
- Application Number
- CN202380059527.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when using dispersants such as surfactants and polyethylene glycol, polyolefin resins are prone to deform during heating stretching and thermal fixation, resulting in cavity collapse, and insufficient lightweight and buffering properties are not achieved. At the same time, poor heat resistance of surfactants and polyethylene glycol leads to thermal deterioration and reduced whiteness, and poor material recirculation.
By adding an extremely small amount of silicone resin to the polyolefin resin, the heat resistance and dispersion thereof are improved, and by adjusting the laminated structure and the addition amount of the silicone resin, deterioration of coating properties and printing properties is suppressed, thereby forming an excellent mold release film.
In the case where the polyolefin resin is used as a hollow developer, it is realized to obtain a release film with excellent environmental correspondence, light weight, film forming, concealment, whiteness and mold release properties, and to improve the recirculation of the material.
Smart Images

Figure BDA0005270195930000201
Abstract
Description
Technical Field
[0001] The present invention relates to a release film containing voids therein, a resin composition obtained by recycling the release film, and a method for producing the resin composition. Background Art
[0002] As a method for obtaining a film having a function similar to that of paper, a method of making a film contain a large number of fine cavities inside is known.
[0003] In this method, an incompatible thermoplastic resin (hereinafter referred to as an incompatible resin) is mixed with a polyester resin to obtain a sheet in which the incompatible resin is dispersed in the polyester resin, and the sheet is stretched in at least a uniaxial direction. Thus, the method causes the voids to be visualized by interfacial peeling between the polyester resin and the incompatible resin. As such incompatible resins, for example, polyolefin resins such as polyethylene resins, polypropylene resins, and polymethylpentene resins (for example, see patent documents 1 to 3), and polystyrene resins (for example, see patent documents 4 and 5) have been proposed. Among them, polypropylene resins are particularly preferred from the aspects of void visualization and cost performance.
[0004] Here, when a polyolefin resin including a polypropylene resin is simply dispersed in a polyester resin, the dispersion diameter of the polyolefin dispersed particles becomes larger. Therefore, the voids are easily visible, but on the other hand, the voids become larger, and sufficient concealment cannot be obtained, and the film-forming property also deteriorates. Therefore, a method of microdispersing the polyolefin resin has begun to be adopted. So far, as a method for the microdispersion, a method of adding a dispersant such as a surfactant or polyethylene glycol has been proposed (for example, refer to Patent Documents 6 and 7).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 49-134755
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2-284929
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 2-180933
[0010] Patent Document 4: Japanese Patent Publication No. 54-29550
[0011] Patent Document 5: Japanese Patent Application Laid-Open No. 11-116716
[0012] Patent Document 6: Japanese Patent Publication No. 7-17779
[0013] Patent Document 7: Japanese Patent Application Laid-Open No. 8-252857 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] However, when a dispersant such as a surfactant or polyethylene glycol is added, although the polyolefin resin has a microdispersion effect, the polyolefin resin will be deformed in the heating and stretching process and the heat fixing process. Therefore, the obtained cavity is also easily crushed, and sufficient lightness and cushioning properties cannot be obtained. In addition, since the heat resistance of surfactants and polyethylene glycol is poor, thermal degradation is easily generated in the melt extrusion process of the polyester resin, and the whiteness of the obtained film is reduced. Depending on the situation, there is a problem of promoting the degradation of the polyester resin and worsening the film-making property.
[0016] In addition, in recent years, from the perspective of the environment, there is a high demand for recyclable films. In particular, there is a demand for recycling films and adding them to resource circulation in the same film. The recyclability of the functional layer coated on the film as a substrate has also become a major technical issue.
[0017] In particular, release films used as separators for labels and the like are discarded after the labels are peeled off, and resource recycling is required. The main reason for discarding them is that the release layer is applied as a functional layer, and the adhesive layer of the label remains on the release film, resulting in poor material recyclability.
[0018] The object of the present invention is to improve the problems of the above-mentioned prior art and provide a release film, a resin composition and a method for producing the resin composition which are excellent in environmental compatibility, lightness, film forming properties, hiding power, whiteness and release properties even when a polyolefin resin is mainly used as a void developing agent and a release layer is provided.
[0019] Solutions for solving problems
[0020] The inventors of the present invention have conducted in-depth research and found that by adding a very small amount of silicone resin to a polyolefin resin, the following is found. That is, the inventors of the present invention have found that the heat resistance of the polyolefin dispersed particles in the polyester resin can be improved, and the deformation of the polyolefin dispersed particles during heating and stretching and heat fixing can be reduced. As a result, the inventors of the present invention have found that a release film with excellent lightness, film-forming properties, concealment and whiteness can be obtained. Furthermore, the inventors of the present invention have found that by adjusting the stacking structure and the amount of silicone resin added, the deterioration of coating and printing properties as side effects of silicone resin can be suppressed. Furthermore, the inventors of the present invention have found that by forming a release layer C from a silicone resin, the silicone resin can be used for the void-containing layer A during recycling. The inventors of the present invention have also found that by recycling the release layer C containing the silicone resin and adding it to the void-containing layer A, the release film can be further lightweight. That is, the inventors of the present invention have found that a release film with excellent environmental compatibility and lightness can be obtained.
[0021] That is, the release film of the present invention includes the following configurations.
[0022] 1. A release film comprising a laminated film and a release layer C provided on at least one side of the laminated film, wherein the laminated film is laminated in this order: a first covering layer B1 comprising a polyester resin containing an inorganic pigment, a void-containing layer A containing voids therein, and a second covering layer B2 comprising a polyester resin containing an inorganic pigment,
[0023] The void-containing layer A is formed of a composition containing a polyester resin, a polyolefin resin and a silicone resin, and the apparent density of the release film is 0.80 g / cm 3 Above and 1.20g / cm 3 the following.
[0024] 2. The release film according to 1. above, wherein the release layer C is formed of a composition containing a silicone resin.
[0025] 3. The release film according to 2. above, wherein the content of the silicone resin in the release layer C is 90% by mass or more and 100% by mass or less relative to the total mass of the release layer C.
[0026] 4. The release film according to 1. above, wherein the silicone resin of the void-containing layer A comprises a silicone resin recycled from the release layer C.
[0027] 5. The release film according to 1. above, wherein in the void-containing layer A, a content of the polydimethylsiloxane in the silicone resin is 1 ppm or more and 2500 ppm or less relative to the total mass of the void-containing layer A.
[0028] 6. The release film according to 1. above, wherein in the void-containing layer A, a content of the polydimethylsiloxane in the silicone resin is 0.005% by mass or more and 2.000% by mass or less relative to 100% by mass of the polyolefin resin.
[0029] 7. The release film according to 1. above, wherein the inorganic pigment in the first covering layer B1 and the second covering layer B2 is titanium oxide or silicon dioxide.
[0030] 8. The release film according to 1. above, wherein the ratio of the total thickness of the first covering layer B1 and the second covering layer B2 to the total thickness of the first covering layer B1, the void-containing layer A, and the second covering layer B2 is 6% or more and 40% or less.
[0031] 9. The release film according to 1. above, wherein a normal peeling force of the surface of the release layer C is 40 mN / 50 mm or more and 400 mN / 50 mm or less.
[0032] 10. The release film according to 1. above, which is used as a separator for labels or a release film for processes.
[0033] 11. A resin composition obtained by recycling the release film according to any one of 1. to 10. above, comprising an inorganic pigment, a polyester resin, a polyolefin resin and a silicone resin.
[0034] 12. A method for producing a resin composition, comprising recycling the release film according to any one of 1. to 10. above to produce a resin composition containing an inorganic pigment, a polyester resin, a polyolefin resin and a silicone resin.
[0035] Effects of the Invention
[0036] The present invention can provide a release film having excellent environmental compatibility, lightness, film forming properties, hiding power, whiteness and release properties even when the film mainly contains a polyolefin resin as a void-forming agent and has a release layer. DETAILED DESCRIPTION
[0037] Hereinafter, the present invention will be described in detail.
[0038] The release film of the present invention is a laminated film and a release layer C laminated in sequence. The laminated film is a polyester film containing voids, which is laminated in sequence with a first coating layer B1 containing a polyester resin containing an inorganic pigment, a void-containing layer A containing voids inside, and a second coating layer B2 containing a polyester resin containing an inorganic pigment. The release layer C is provided on at least one side of the laminated film. The void-containing layer A contains a composition containing a polyester resin, a polyolefin resin, and a silicone resin. In addition, the apparent density of the release film is 0.80 g / cm 3 Above and 1.20g / cm 3 the following.
[0039] The polyester resin that is the main component of the void-containing layer A, the first covering layer B1, and the second covering layer B2 is a polymer synthesized from a dicarboxylic acid or an ester-forming derivative thereof and a diol or an ester-forming derivative thereof. Representative examples of such polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate. Among them, polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, and the like.
[0040] In addition, other components may be copolymerized in these polyester resins within the scope that does not impair the purpose of the present invention. Specifically, as copolymerization components, among the dicarboxylic acid components, isophthalic acid, naphthalene dicarboxylic acid, 4,4-diphenyl dicarboxylic acid, adipic acid, sebacic acid and its ester-forming derivatives can be listed. In addition, as diol components, diethylene glycol, hexamethylene glycol, neopentyl glycol, cyclohexanedimethanol can be listed. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol can also be listed. As the copolymerization amount, it is preferably within 10 mol% relative to the repeating unit constituted, and more preferably within 5 mol%. As the polyester resin, plastic bottle recycled raw materials can be used.
[0041] The polyester resin is produced by, for example, firstly using the above-mentioned dicarboxylic acid or its ester-forming derivative and diol or its ester-forming derivative as main starting materials, then subjecting them to esterification or transesterification reaction according to a conventional method, and then subjecting them to polycondensation reaction at high temperature and reduced pressure.
[0042] From the viewpoint of film forming properties, recycling properties, etc., the intrinsic viscosity of the polyester resin is preferably 0.50 dl / g to 0.9 dl / g, more preferably 0.55 dl / g to 0.85 dl / g.
[0043] The content of the polyester resin is preferably 70% by mass or more and 97% by mass or less, and more preferably 75% by mass or more and 95% by mass or less, relative to 100% by mass of the total of all components contained in the void-containing layer A. When the content of the polyester resin is 70% by mass or more, the release film can suppress the deterioration of film-forming properties. When the content of the polyester resin is 97% by mass or less, the release film can form voids by adding a polyolefin resin and a silicone resin.
[0044] Next, the incompatible resin used as the void developing agent in the present invention, i.e., the polyolefin resin, is described. The release film of the present invention can maintain void developing properties by adopting a specific layer structure and using a specific polyolefin resin. The polyolefin resin is, for example, a polyethylene resin, a polypropylene resin, etc., preferably a polypropylene resin. As a result, the release film of the present invention can obtain sufficient lightness and cushioning properties, and has excellent film forming properties, concealing properties, and whiteness.
[0045] The polyolefin resin used in the present invention is preferably a crystalline polyolefin having 95 mol% or more, more preferably 98 mol% or more of olefin units, and is particularly preferably a crystalline polyolefin homopolymer having 100 mol% of olefin units.
[0046] From the viewpoint of void visibility and film forming properties, the melt flow rate (MFR) of the polyolefin resin used in the present invention is preferably 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, and more preferably 1.5 g / 10 minutes or more and 7.0 g / minute or less. When the MFR is 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, the polyolefin dispersed particles become difficult to deform when extruded from the die, and thus become easy to form voids. Furthermore, when the MFR is 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, the dispersibility of the polyolefin dispersed particles is also excellent, and sufficient concealment and excellent film forming properties can be obtained. It should be noted that the melt flow rate (MFR) is a measured value based on JIS K 7210 at 230°C and a load of 2.16 kg.
[0047] From the viewpoint of void visualization, the load deflection temperature of the polyolefin resin used in the present invention is preferably 85°C or more, more preferably 90°C or more, and further preferably 95°C or more. The upper limit is not particularly limited, but is preferably 135°C or less. When the load deflection temperature is 85°C or more, especially in the longitudinal stretching process of stretching the film by heating above the glass transition temperature of the polyester resin described later, the polyolefin dispersed particles become difficult to break, and thus become easy to form voids. It should be noted that the load deflection temperature is a measured value when the bending stress of the test piece is 0.45MPa according to the B method of JIS K 7191-1, 2.
[0048] From the viewpoint of void visualization, suppressing thermal degradation in the extrusion process and the recovery process, the weight average molecular weight (Mw) of the polyolefin resin used in the present invention is preferably 200000 or more and 450000 or less, more preferably 250000 or more and 400000 or less. When Mw is 450000 or less, the dispersibility of the polyolefin dispersed particles becomes good, sufficient concealment can be obtained, and excellent film forming properties are obtained. When Mw is 200000 or more, the polyolefin dispersed particles become difficult to deform, and therefore become easy to form voids. When Mw is 200000 or more, even when recycled raw materials are used, it is possible to suppress the decrease in void visualization, so it is preferred.
[0049] In addition, the ratio of weight average molecular weight (Mw) and number average molecular weight (Mn), i.e. molecular weight distribution (Mw / Mn) is preferably 2 or more and 6 or less, more preferably 2 or more and 5 or less. Mw / Mn represents an index of the width of molecular weight distribution, and the larger the value, the wider the molecular weight distribution. When Mw / Mn is less than 6, since low molecular weight components are reduced, even when recycled raw materials are used, the reduction of whiteness and void visibility can be suppressed, so it is preferred. In addition, when Mw / Mn is more than 2, it is suitable for industrial production from the viewpoint of cost. It should be noted that weight average molecular weight (Mw) and number average molecular weight (Mn) are values measured by gel permeation chromatography (GPC).
[0050] From the viewpoint of void visualization and film forming properties, the content of the polyolefin resin is preferably 3% by mass or more and 30% by mass or less, and more preferably 5% by mass or more and 25% by mass or less, relative to 100% by mass of the total of all components contained in the void-containing layer A. When the content of the polyolefin resin is 3% by mass or more and 30% by mass or less, voids for obtaining sufficient lightness and cushioning properties can be formed, and film forming properties are excellent.
[0051] Examples of the silicone resin used in the present invention include silicone polymers, such as partially cross-linked silicone polymers (i.e., silicone resins in a narrow sense) and linear silicone polymers (i.e., silicone rubber). Specifically, examples include methyl silicone resins, methylphenyl silicone resins, phenyl silicone resins, alkyd-modified silicone resins, polyester-modified silicone resins, urethane-modified silicone resins, epoxy-modified silicone resins, and acrylic-modified silicone resins. From the viewpoint of withstanding the extrusion temperature of the polyester resin as the base resin and the viewpoint of suppressing process contamination caused by sublimation, silicone resins having a cross-linked structure are preferred.
[0052] There is no particular limitation on the method of adding the silicone resin, and the silicone resin may be added directly by dry-mixing a powdery or granular material with the base resin. A masterbatch may be prepared in advance by melt-mixing a polyester resin, a polyolefin resin, and a silicone resin. The silicone resin contained in the release layer of a release polyester film may be recycled together with the polyester film, and the obtained polyester granules containing the silicone resin may be added.
[0053] From the viewpoint of void visibility, film forming property, and manufacturing cost, the amount of silicone resin added is preferably 1 ppm or more and 10000 ppm or less, and more preferably 100 ppm or more and 8000 ppm or less relative to the total mass of the void-containing layer A. By setting it to more than 1 ppm, the apparent density can be efficiently reduced. By setting it to less than 10000 ppm, the deterioration of process pollution and film forming property can be suppressed. The manufacturing cost can be further suppressed.
[0054] The content of polydimethylsiloxane from silicone resin is obtained by NMR (nuclear magnetic resonance) method. From the viewpoint of void visualization, film forming property and manufacturing cost, the content of polydimethylsiloxane from silicone resin is preferably 1 ppm or more and 2500 ppm or less, more preferably 100 ppm or more and 2400 ppm or less relative to the total mass of void-containing layer A. It is further preferably 100 ppm or more and 1400 ppm or less. The upper limit of the content of polydimethylsiloxane from silicone resin is preferably 2500 ppm, more preferably 2400 ppm, and more preferably 1400 ppm. The lower limit of the content of polydimethylsiloxane from silicone resin is preferably 1 ppm, and more preferably 100 ppm.
[0055] By setting it to 1ppm or more, the apparent density can be efficiently reduced. By setting it to 2500ppm or less, the process pollution and the deterioration of the film forming property can be suppressed. The manufacturing cost can be further suppressed. The silicone resin has a cross-linked structure and is insoluble in the solvent. Therefore, the NMR measurement method described later is used to obtain the content of polydimethylsiloxane present in the silicone resin, which can be used as an indicator of the content of the silicone resin in the void-containing layer A.
[0056] The content of polydimethylsiloxane in the silicone resin contained in the void-containing layer A obtained by the NMR method is preferably 0.005% by mass or more and 2.000% by mass or less relative to 100% by mass of the polyolefin resin in the void-containing layer A. It is further preferably 0.010% by mass or more and 1.800% by mass or less. It is further preferably 0.100% by mass or more and 0.800% by mass or less. The upper limit of the content of polydimethylsiloxane in the silicone resin contained in the void-containing layer A obtained by the NMR method is preferably 2.000% by mass, more preferably 1.800% by mass, and further preferably 0.800% by mass. The lower limit of the content of polydimethylsiloxane in the silicone resin contained in the void-containing layer A obtained by the NMR method is preferably 0.005% by mass, more preferably 0.010% by mass, and further preferably 0.100% by mass.
[0057] By containing 0.005 mass % or more relative to 100 mass % of the polyolefin resin, the heat resistance of the polyolefin resin can be improved, and voids can be efficiently developed without being crushed during stretching. By setting the content to 2.000 mass % or less, deterioration of film forming properties can be suppressed.
[0058] The void-containing layer A can impart heat resistance to the polyolefin resin by containing a trace amount of silicone resin. Therefore, when the release film material is reused, the silicone resin has the effect of suppressing the thermal degradation of the polyolefin resin and maintaining the void visualization. Even if it is made into a release film, the void is difficult to be crushed in a high temperature environment, so the uneven thickness caused by the local crushing of the polyolefin resin as a void visualization agent can be suppressed.
[0059] In addition, incompatible resins other than polyolefin resins may be contained within the scope of not impairing the purpose of the present invention. The polyolefin resin preferably contains 90% by mass or more, more preferably 95% by mass or more, and most preferably 100% by mass relative to the total amount of 100% by mass of incompatible resins in the void-containing layer A. In addition, from the viewpoint of whiteness and void visualization, it is preferred that dispersants such as polyethylene glycol and surfactants are not contained.
[0060] In addition, within the scope of not impairing the purpose of the present invention, these polyester resins or polyolefin resins may contain a small amount of other polymers, antioxidants, heat stabilizers, matting agents, pigments, ultraviolet absorbers, fluorescent whitening agents, plasticizers or other additives. In particular, in order to suppress the oxidative degradation of polyolefin resins, it is preferred to contain an antioxidant or a thermal stabilizer. There is no particular limitation on the types of antioxidants and thermal stabilizers, for example, hindered phenol systems, phosphorus systems, hindered amine systems, etc. can be listed, and they can be used alone or in combination. As an added amount, it is preferably more than 1ppm and less than 50000ppm relative to the total mass of the void-containing layer A. It should be noted that in the present invention, even if a fluorescent whitening agent is not added to the void-containing layer A, excellent whiteness can be ensured.
[0061] In the present invention, in the demoulding film, in order to improve concealment and whiteness, inorganic pigments can be contained in the polyester resin or the polyolefin resin as required. As inorganic pigments, silicon dioxide, kaolinite, talc, calcium carbonate, zeolite, aluminum oxide, barium sulfate, titanium oxide, zinc sulfide, etc. can be listed. Among these, silicon dioxide, titanium oxide, calcium carbonate, and barium sulfate are preferred from the viewpoint of concealment and whiteness. In addition, these inorganic pigments can be used alone, or two or more can be used in combination. These inorganic pigments can be contained in the demoulding film by being added to the polyester resin or the polyolefin resin in advance.
[0062] The method of mixing the inorganic pigment into the polyester resin or the polyolefin resin is not particularly limited, and the following methods can be cited, that is, a method of directly feeding the polyester resin and the polyolefin resin into a film-making machine after dry blending, a method of dry blending the polyester resin and the polyolefin resin and then melt-blending them using various common mixers to form a masterbatch, etc.
[0063] The release film of the present invention has a laminated structure in which a first coating layer B1 including a polyester resin containing an inorganic pigment, a void-containing layer A containing voids inside, and a second coating layer B2 including a polyester resin containing an inorganic pigment are sequentially laminated. Here, when the void-containing layer A containing a polyolefin resin is exposed on the surface layer, a part of the exposed polyolefin dispersed particles may cause process contamination such as roller contamination. In addition, by coating the void-containing layer A with the first coating layer B1 containing an inorganic pigment and the second coating layer B2, it is possible to prevent the whiteness from being reduced. The first coating layer B1 and the second coating layer B2 may be layers of the same composition or layers of different compositions.
[0064] From the viewpoint of void visibility and exposure suppression of polyolefin resin and silicone resin, the ratio of the total thickness of the first coating layer B1 and the second coating layer B2 to the total thickness of the first coating layer B1, the thickness of the void-containing layer A and the thickness of the second coating layer B2 (hereinafter sometimes referred to as the layer ratio) is preferably 6% or more and 40% or less, and more preferably 8% or more and 30% or less. When the layer ratio is 6% or more and 40% or less, the exposure of polyolefin resin and silicone resin can be suppressed, and the contact angle of water and the contact angle of diiodomethane can be reduced. Furthermore, when the layer ratio is 6% or more and 40% or less, it is easy to form voids for obtaining sufficient lightness and cushioning properties.
[0065] As the inorganic pigment contained in the first coating layer B1 and the second coating layer B2, silicon dioxide, kaolinite, talc, calcium carbonate, zeolite, aluminum oxide, barium sulfate, titanium oxide, zinc sulfide, etc. can be listed. Among them, from the viewpoint of concealment and whiteness, titanium oxide, calcium carbonate, barium sulfate are preferred, and titanium oxide is particularly preferred. In addition, these inorganic pigments can be used alone, or two or more can be used in combination. These pigments can be contained in the film by being added to the polyester resin in advance.
[0066] The amount of the inorganic pigment added to the first covering layer B1 is not particularly limited, but is preferably 1% by mass or more and 35% by mass or less, and more preferably 2% by mass or more and 30% by mass or less, relative to 100% by mass of all components constituting the first covering layer B1. When the amount of the inorganic pigment added is 1% by mass or more and 35% by mass or less, it is easy to improve the concealing property and whiteness of the release film, and it is also possible to improve the film forming property and mechanical strength of the release film.
[0067] The amount of the inorganic pigment added to the second covering layer B2 is not particularly limited, but is preferably the same as the amount of the inorganic pigment added to the first covering layer B1.
[0068] The laminated film of the present invention has a release layer C on at least one side. Therefore, the release film can have the following laminated structure. That is, it can have a laminated structure in which the release layer C, the first coating layer B1, the void-containing layer A and the second coating layer B2 are laminated in the order of C / B1 / A / B2 or B1 / A / B2 / C.
[0069] The release layer C is preferably composed of a composition containing a silicone resin. Examples of the silicone resin used in the release layer C include silicone polymers, such as partially cross-linked silicone polymers (i.e., silicone resins as silicone resins in a narrow sense) and linear silicone polymers (i.e., silicone rubbers). Specifically, examples include methyl silicone resins, methylphenyl silicone resins, phenyl silicone resins, alkyd-modified silicone resins, polyester-modified silicone resins, urethane-modified silicone resins, epoxy-modified silicone resins, and acrylic-modified silicone resins. From the viewpoint of forming the release layer C by coating, a heat-addition-type silicone resin cross-linked by applying heat is preferred.
[0070] The silicone resin constituting the release layer C is preferably 90% to 100% by mass, more preferably 94% to 100% by mass, relative to the total resin in the release layer C. By setting it to 90% by mass or more, it can be peeled off without leaving any adhesive residue when peeling a label or the like.
[0071] In addition, a resin composition that is recycled together with the release layer can be used. The resin composition is, for example, in the form of pellets and contains an inorganic pigment, a polyester resin, a polyolefin resin, and a silicone resin. It is known that when the resin composition is added to the base film, the silicone resin contained in the release layer plays a role in reducing the apparent density of the base film.
[0072] The coating amount of the release layer C is preferably 0.030 g / m 2 Above and 0.200g / m 2 Below, more preferably 0.050g / m 2 Above and 0.150g / m 2 Below. By setting it to 0.030g / m 2 The above can be peeled off without adhesive residue when peeling off the label or the like. 2 Next, the label can be made difficult to peel off.
[0073] As a method for providing a coating layer, commonly used methods such as gravure coating, kiss coating, dipping, spraying, curtain coating, air knife coating, blade coating, reverse roll coating, etc. can be applied. As a coating stage, any method such as a method of coating before stretching the film, a method of coating after longitudinal stretching, and a method of coating on the surface of the film after the stretching treatment can be applied.
[0074] The normal peeling force of the release surface coated with the release layer C under a 25°C 40% RH environment is preferably 40 mN / 50 mm or more and 400 mN / 50 mm or less, and more preferably 50 mN / 50 mm or more and 350 mN / 50 mm or less. By setting it to 40 mN / 50 mm or more, it is possible to peel off without adhesive residue when peeling off a label or the like. By setting it to 400 mN / 50 mm or less, it is possible to make the label difficult to peel off.
[0075] In addition, in the release film of the present invention, a coating layer may be provided on the opposite side of the surface of the release layer C in order to prevent static electricity. As a compound constituting the coating layer, a polyester resin is preferred. In addition, polyurethane resin, polyester urethane resin, acrylic resin, etc., which are generally disclosed as means for improving the adhesiveness of polyester films, can also be used.
[0076] As a method for providing a coating layer, commonly used methods such as gravure coating, kiss coating, dipping, spraying, curtain coating, air knife coating, blade coating, reverse roll coating, etc. can be applied. As a coating stage, any method such as a method of coating before stretching the film, a method of coating after longitudinal stretching, and a method of coating on the surface of the film after the stretching treatment can be applied.
[0077] The method for producing the release film of the present invention is described. For example, after drying the mixed pellets formed by the composition containing polyester resin, polyolefin resin and silicone resin, the mixed pellets are melt-extruded from a T-shaped nozzle into a sheet, and the sheet is made to adhere to a casting drum by an electrostatic application method, etc. and cooled and solidified to obtain an unstretched film.
[0078] Next, the unstretched film is stretched / oriented. The following is an example of the most commonly used sequential biaxial stretching method, especially the method of longitudinally stretching the unstretched film in the length direction and then transversely stretching it in the width direction. First, in the longitudinal stretching process in the length direction, the film is heated and stretched to 2.5 to 5.0 times between two or more rollers with different peripheral speeds. As the heating means at this time, it can be a method using a heated roller, or a method using a non-contact heating medium, or a combination of them. At this time, it is preferred to set the temperature of the film to the range of (Tg-10°C) to (Tg+50°C). Next, the uniaxially stretched film is introduced into a tenter and stretched to 2.5 to 5 times in the width direction at a temperature below (Tg-10°C) to Tm-10°C, thereby obtaining a biaxially stretched film.
[0079] Here, Tg is the glass transition temperature of the polyester resin, and Tm is the melting point of the polyester. The film obtained as described above is preferably subjected to heat treatment as necessary, and the treatment temperature is preferably within the range of (Tm-60°C) to Tm.
[0080] In addition, the laminated film of the present invention may contain recycled materials composed of used release films of the present invention in the void-containing layer A. Used release films of the present invention refer to release films that are intended to be discarded after the label is peeled off, for example. In addition, film scraps generated by edge parts, fractures, etc. generated during the film-making process can also be used as recycled materials.
[0081] In the case of adding recycled raw materials to the void-containing layer A, if the recycled raw materials of the release film of the present invention are used, since a small amount of silicone resin is added to the polyolefin resin, the void visualization can be maintained. In particular, since the release layer C composed of silicone resin is coated, the silicone resin contained in the release layer C can further assist the void visualization. As a result, the release film can obtain sufficient lightness and cushioning properties, and a release film with excellent concealment and whiteness can be obtained. Especially today when it is required to cope with environmental loads, the amount of recycled raw materials added is increased compared to the past because the used release film is recycled. However, if silicone resin is added, the void visualization can be maintained even when the amount added is increased.
[0082] The amount of the recycled raw material added is preferably 5 to 80% by mass relative to 100% by mass of the total mass of the void-containing layer A from the viewpoint of reducing the raw material cost, whiteness, and film forming properties.
[0083] The first covering layer B1 or the second covering layer B2 may contain recycled materials, but preferably contain no recycled materials from the viewpoint of deterioration of whiteness and exposure of polyolefin resin in the recycled materials.
[0084] The apparent density of the release film in the present invention is preferably 0.80 g / cm 3 Above and 1.2g / cm 3 Below, more preferably 0.80g / cm 3 Above and 1.10g / cm 3 Below. Apparent density is 0.80g / cm 3 Above and 1.20g / cm 3 In the case of the following, the total voids in the release film are appropriate, and it becomes easy to handle during post-processing such as printing and use. In addition, the apparent density is 0.80 g / cm 3 Above and 1.20g / cm 3 In the following cases, sufficient lightness and cushioning properties can be obtained.
[0085] In particular, the release film of the present invention contains a small amount of silicone resin, and thus has excellent lightness, film-forming properties, hiding power, and whiteness even when the apparent density is 0.80 to 1.10.
[0086] In addition, the apparent density is a value obtained by the measuring method described in the evaluation method mentioned later.
[0087] The total light transmittance of the release film of the present invention is preferably 30% or less, more preferably 25% or less. When the total light transmittance is 30% or less, sufficient concealment can be obtained. For example, when used for labels, the image printed on the labels becomes more distinct. It should be noted that the total light transmittance is a value converted to a thickness of 50 μm obtained by the measurement method described in the evaluation method described later.
[0088] The release film of the present invention preferably has a hue b value of 4.0 or less, more preferably 3.0 or less. If the hue b value is greater than 4.0, the whiteness is poor, and when used as a label, the clarity during printing may be reduced, which may impair the product value.
[0089] The thickness of the release film of the present invention is arbitrary, but is preferably 20 μm or more and 300 μm or less.
[0090] As described above, in the release film of the present invention, the void-containing layer A contains a trace amount of silicone resin, which can suppress the thermal degradation of the polyolefin resin during the processing step, for example, and maintain the void visibility. Therefore, the release film of the present invention has excellent lightness, film forming properties, concealing properties, and whiteness even if the apparent density is 0.80 to 1.20.
[0091] Therefore, the release film of the present invention is suitable for use as a separator for a label, a release film used in the production of a polarizing plate or a laminated ceramic capacitor.
[0092] In addition, the present invention can also adopt a manufacturing method of recycling the release film of the present invention to generate a resin composition. The resin composition is, for example, in the form of pellets, and contains an inorganic pigment, a polyester resin, a polyolefin resin, and a silicone resin. Specifically, the manufacturing method includes, for example, crushing the release film of the present invention into a specified size using a crusher, supplying it to a single-axis or double-axis extruder, extruding it at a specified temperature, cooling it, and then granulating it into pellets using a granulator. The specified size is, for example, 16 mm 2 Above and 64mm 2 The predetermined temperature is, for example, 250° C. or higher and 300° C. or lower.
[0093] Example
[0094] The present invention is specifically described below by giving examples. It should be noted that the present invention is not limited to the examples described below. It should be noted that each evaluation item in the examples and comparative examples was measured by the following methods.
[0095] (1) Film-forming properties
[0096] The evaluation was performed as follows based on the number of breakages during the film production process with a film production time of 2 hours under the film production conditions described in the laminated thin film production described later.
[0097] ○: No breakage
[0098] △: Broken 1 to 3 times
[0099] ×: Broken more than 4 times, unable to form film
[0100] (2) Apparent density
[0101] Cut the release film into 4 pieces of 5.0 cm square, overlap the 4 pieces, use a micrometer to change the total thickness position to 4 significant figures to measure 10 points, and find the average thickness of the 4 overlapping pieces. Divide the average value by 4, round it to 3 significant figures, and use it as the average thickness of each piece (t: μm). Use an automatic plate balance to measure the mass (w: g) of the 4 pieces of the sample to 4 significant figures, and find the apparent density by the following formula. It should be noted that the apparent density is rounded to 3 significant figures.
[0102] Apparent density (g / cm 3 ) = w / (5.0×5.0×t×10 -4 ×4)
[0103] (3) Total light transmittance
[0104] The release film was measured using a haze meter (NDH5000 manufactured by Nippon Denshoku Industries Co., Ltd.) and converted into a value per 50 μm of film thickness. The same measurement was performed three times, and the arithmetic mean value was adopted.
[0105] (4) Hue b value
[0106] The color tone b value was measured on the opposite side of the release layer C of the release film using a colorimeter (ZE6000) manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS-8722. The smaller the color tone b value, the higher the whiteness and the weaker the yellowness.
[0107] (5) Determination of polydimethylsiloxane content in layer A
[0108] After the release layer C is physically cut off with a cutter, the laminated film is dissolved in 0.1 ml of CDCl3 (deuterated chloroform) / HFIP-d (deuterated hexafluoroisopropanol) (1 / 1 volume ratio), and then 0.5 ml of TCE (tetrachloroethane)-d is added and dissolved at 130°C. The solution is subjected to H-NMR measurement at 120°C, and the mass ratio of polydimethylsiloxane is calculated from the ratio of the integral values of the obtained components. The peak of polydimethylsiloxane is the peak detected near 0.2 ppm of the NMR spectrum. The content of polydimethylsiloxane in the void-containing layer A is calculated as follows: After the release layer C is physically cut with a cutter, a cross-section observation is performed, and the thickness of the A layer, the B1 layer, and the B2 layer are measured, and the layer ratio calculated thereby is used for calculation. Since the silicone resin has a large amount of cross-linked and insoluble components, it is difficult to quantify the amount of addition, but if the above method is used, the polydimethylsiloxane of the soluble component in the silicone resin can be quantified. It can be confirmed that the amount of silicone resin added is correlated with the content of polydimethylsiloxane.
[0109] (6) Determination of the mass ratio of polypropylene resin content to polydimethylsiloxane content
[0110] H-NMR measurement was performed in the same manner as above except that the mold release layer C was not scraped off, and the mass ratio was calculated from the ratio of the integrated values of the peaks of the polypropylene resin and the polydimethylsiloxane in the obtained NMR spectrum.
[0111] (7) Evaluation of normal peeling force of release surface
[0112] The surface of the release layer C of the release film was laminated on the adhesive layer of an acrylic adhesive tape (Nitto 31B, 25 mm wide, manufactured by Nitto Denko Corporation) (hereinafter sometimes referred to as "release surface"), and a 5 kg iron cylinder was rolled back and forth once, and then placed under the conditions of 20°C and 15% RH for 24 hours, and then the peeling load when peeled at a peeling angle of 90 degrees and a tensile speed of 300 mm / min was measured using Tensilon. The obtained value was multiplied by 2 and the unit was converted into mN / 50mm.
[0113] (Example 1)
[0114] [Manufacture of titanium oxide masterbatch (M1)]
[0115] 50% by mass of anatase-type titanium dioxide having an average particle size of 0.3 μm (by electron microscopy) was mixed with 50% by mass of polyethylene terephthalate resin having an intrinsic viscosity of 0.62, and the mixture was supplied to a vented twin-screw extruder for kneading to produce a masterbatch (M1) containing titanium oxide.
[0116] [Manufacturing of Silicone Resin S]
[0117] A thermosetting silicone resin (KS-774 manufactured by Shin-Etsu Chemical Co., Ltd.) was diluted with a solvent, and 3 parts by mass of a catalyst (CAT-PL-3 manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts by mass of the silicone resin, and heated at 150° C. for 60 seconds. After the heating, the cured silicone resin was powdered to obtain a silicone resin S.
[0118] [Manufacturing of unstretched film]
[0119] 93% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62, 6.92% by mass of polypropylene resin with MFR=2.5, Mw=320000, Mw / Mn=4.0, and load deflection temperature=92°C, and 800ppm of silicone resin S are mixed. Then, the mixture is vacuum dried and used as a raw material for the void-containing layer A. On the other hand, 30% by mass of the above-mentioned masterbatch (M1) containing titanium oxide and 70% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62 are pelletized and mixed. Then, the mixture is vacuum dried and used as a raw material for the first covering layer B1 and the second covering layer B2. These raw materials are supplied to their respective extruders, melted at 285°C, and stacked in the order of B1 / A / B2 for the first covering layer B1, the void-containing layer A, and the second covering layer B2. The stack is joined by a feed head in a manner such that the thickness ratio becomes 10 / 80 / 10. This bonded body was extruded from a T-die onto a cooling drum adjusted to 30° C. to produce two types of three-layered unstretched films.
[0120] [Laminated film production]
[0121] The laminated film was prepared under the following film-making conditions. That is, the obtained unstretched film was uniformly heated to 70°C using a heating roller, and longitudinally stretched to 3.4 times between two pairs of clamping rollers with different peripheral speeds. At this time, as an auxiliary heating device for the unstretched film, an infrared heater (rated at 20W / cm) with a gold reflective film in the middle of the clamping roller was set opposite to both sides of the film (at a distance of 1 cm from the film surface) to heat it. The uniaxially stretched film thus obtained was introduced into a tenter, heated to 140°C, stretched to 4.0 times in the transverse direction, fixed in width, heat treated at 235°C, and then relaxed by 3% in the width direction at 210°C, thereby obtaining a laminated film with a thickness of 50μm.
[0122] [Release film production]
[0123] A curable silicone resin (KS-774 manufactured by Shin-Etsu Silicone Co., Ltd.) was diluted in a mixed solvent of methyl ethyl ketone and toluene, and a catalyst (CAT-PL-3 manufactured by Shin-Etsu Chemical Co., Ltd.) was added to the solution at a total solid content concentration of 1.5% by mass relative to 100% by mass of the silicone resin. The mold release layer C was coated by a conventional roll coating method so that the thickness of the mold release layer after drying was 0.10 g / m 2 The solution was applied to one side of the laminated film in a manner of . Thus, a release film was obtained in which the release layer C, the first coating layer B1, the void-containing layer A, and the second coating layer B2 were laminated in the order of C / B1 / A / B2. The heat drying by the roll coating method was performed at 150° C. for 20 seconds. The results of the apparent density, the normal peeling force of the release surface, the color tone b value, the total light transmittance, and the film forming properties are shown in Table 1.
[0124] [Production of recycled materials]
[0125] The release film prepared in Comparative Example 1 below was placed in a pulverizer and pulverized at a rate of 100 kg / hour using a 4 mm mesh screen to obtain a pulverized film. The pulverized film was fed into an extrusion granulator to obtain a recycled raw material.
[0126] (Examples 2, 3, 5, 7, 8)
[0127] In Example 1, except that the raw material ratio of the void-containing layer A was changed as shown in Table 1, the same method as in Example 1 was carried out to obtain a release film.
[0128] (Example 4)
[0129] In Example 1, except that the raw material ratio and the layer ratio of the void-containing layer A were changed as shown in Table 1, a release film was obtained in the same manner as in Example 1.
[0130] (Example 6)
[0131] A release film was obtained in the same manner as in Example 1 except that the coating amount for forming the release layer C was changed to half of that in Example 1.
[0132] (Example 9)
[0133] In Example 1, the raw material ratio of the void-containing layer A was the same, but 31% of a recycled raw material of plastic bottles was used as a part of the polyethylene terephthalate, and a void-containing polyester film was obtained in the same manner as in Example 1.
[0134] (Example 10)
[0135] [Manufacture of silica-containing masterbatch (M2)]
[0136] 7200 ppm of silica having an average particle size of 3.4 μm was mixed with a polyethylene terephthalate resin having an intrinsic viscosity of 0.62, and the mixture was supplied to a vented twin-screw extruder for kneading to produce a silica-containing masterbatch (M2).
[0137] In the manufacture of the unstretched film, 91.5% by mass of the above-mentioned silica-containing masterbatch (M2) and 8.5% by mass of a polyethylene terephthalate resin having an intrinsic viscosity of 0.62 were pelletized and mixed. The mixture was then vacuum dried to prepare the first covering layer B1 and the second covering layer B2. A void-containing polyester film was obtained in the same manner as in Example 1 except for the above.
[0138] (Comparative Example 1)
[0139] In Example 1, a release film was obtained in the same manner as in Example 1 except that the silicone resin in the void-containing layer A was changed to 0 ppm and the polyethylene terephthalate resin was changed to 93.08 mass %. The apparent density of the release film of Comparative Example 1 exceeded 1.20 g / cm 3 , so it is out of the scope of the present invention. Therefore, the lightness and cushioning properties are poor. Since the mass is large, the manufacturing cost is also increased.
[0140] (Comparative Example 2)
[0141] In Example 1, a release film was obtained in the same manner as in Example 1 except that the raw material ratio of the void-containing layer A was changed as shown in Table 1. In Comparative Example 2, the content of polydimethylsiloxane in the silicone resin in the void-containing layer A exceeded 2500 ppm relative to the total mass of the void-containing layer A, and therefore was outside the scope of the present invention. Therefore, the film forming properties of Comparative Example 2 were inferior to those of Examples 1 to 10.
[0142] According to the above, the release film of the present invention can maintain the void visibility by making the void-containing layer A contain a trace amount of silicone resin, for example, by suppressing the thermal degradation of the polyolefin resin during the processing step. Therefore, the release film of the present invention has excellent lightness, film-forming properties, concealment and whiteness even if the apparent density is 0.80 to 1.20. In particular, the release films of Examples 2 to 5 have excellent lightness, film-forming properties, concealment and whiteness even if the apparent density is 0.80 to 1.10.
[0143] [Table 1]
[0144]
[0145] Industrial Applicability
[0146] As described above, the release film of the present invention is excellent in environmental compatibility, lightness, film forming properties, concealing properties, whiteness, and release properties, and is therefore suitable for use as a release film used in the manufacture of, for example, label separators, polarizing plates, and laminated ceramic capacitors.
Claims
1. A release film comprising a laminate film and a release layer C provided on at least one side of the laminate film, The laminated film is laminated in this order: a first covering layer B1 including a polyester resin containing an inorganic pigment, a void-containing layer A containing voids therein, and a second covering layer B2 including a polyester resin containing an inorganic pigment. The void-containing layer A is formed of a composition containing a polyester resin, a polyolefin resin, and a silicone resin. The apparent density of the release film is 0.80 g / cm 3 Above and 1.20g / cm 3 the following.
2. The release film according to claim 1, wherein The release layer C is formed from a composition containing a silicone resin.
3. The release film according to claim 2, wherein In the release layer C, the content of the silicone resin is 90% by mass or more and 100% by mass or less relative to the total mass of the release layer C.
4. The release film according to claim 1, wherein The silicone resin of the void-containing layer A includes the silicone resin recycled from the release layer C.
5. The release film according to claim 1, wherein In the void-containing layer A, the content of the polydimethylsiloxane in the silicone resin is 1 ppm or more and 2500 ppm or less relative to the total mass of the void-containing layer A.
6. The release film according to claim 1, wherein In the void-containing layer A, the content of the polydimethylsiloxane in the silicone resin is 0.005 mass % or more and 2.000 mass % or less relative to 100 mass % of the polyolefin resin.
7. The release film according to claim 1, wherein The inorganic pigment in the first covering layer B1 and the second covering layer B2 is titanium oxide or silicon dioxide.
8. The release film according to claim 1, wherein The ratio of the total thickness of the first covering layer B1 and the second covering layer B2 to the total thickness of the first covering layer B1, the void-containing layer A, and the second covering layer B2 is 6% to 40%.
9. The release film according to claim 1, wherein The normal peeling force of the surface of the release layer C is 40 mN / 50 mm or more and 400 mN / 50 mm or less.
10. The release film according to claim 1, characterized in that It is used as a separator for labels or a release film for processes. 11 . A resin composition obtained by recycling the release film according to claim 1 , comprising an inorganic pigment, a polyester resin, a polyolefin resin and a silicone resin.
12. A method for producing a resin composition, wherein: The release film according to any one of claims 1 to 10 is recycled to produce a resin composition containing an inorganic pigment, a polyester resin, a polyolefin resin and a silicone resin.
Citation Information
Patent Citations
JP1974134755A
JP1979029550B1
White surface-roughened polyester film and its production
JP1990180933A
White polyester film
JP1990284929A
Microbubble-containing polyester film
JP1995017779B2